Pharmacokinetics and safety of the sesame lignans, sesamin and episesamin, in healthy subjects - Tomimori, Namino; Tanaka, Yasuhiro; Kitagawa, Yoshinori; Fujii, Wataru; Sakakibara, Yutaka; Shibata, Hiroshi (Biopharmaceutics & drug disposition, 2013)
ABSTRACT A single‐blind, placebo‐controlled, parallel‐group and multiple oral dose study was conducted in 48 healthy subjects to investigate the pharmacokinetics and safety of multiple oral doses of sesame lignans (sesamin and episesamin). Subjects were randomly divided into two groups. Each subject was administered 50 mg of sesame lignans (sesamin/episesamin = 1/1) or placebo once daily for 28 days. The pharmacokinetics of the sesame lignans were investigated using 10 of the 24 subjects in the sesame lignans group. No serious adverse events were observed in this study. Sesamin was absorbed with a peak plasma concentration at 5.0 h. The plasma concentration of the main metabolite, SC‐1, reached a peak at 5.0 h and decreased rapidly with a terminal half‐life of 2.4 h. Episesamin was also absorbed with a peak plasma concentration at 5.0 h and decreased with a terminal half‐life of 7.1 h. The plasma concentration of the main metabolite, EC‐1, reached a peak at 5.0 h and decreased rapidly with a terminal half‐life of 3.4 h. The plasma concentrations of sesamin and episesamin reached a steady state by day 7. Sesame lignans were confirmed to be safe and tolerable in healthy subjects. The results of the pharmacokinetic study demonstrate that no accumulation was observed following multiple 50 mg doses of sesame lignans. Copyright © 2013 John Wiley & Sons, Ltd.